THE TAXATION AND THE COUNTRIES COMPETITIVENESS - Csongor CSŐSZ; Tímea RÉTI (Management Intercultural, 2017)

(untitled)
According to the OECD, competitiveness is a measure of a country's advantage or disadvantage in selling its products on international markets. While economists consider productivity and growth rate as basic indicators of competitiveness, those dealing with economic- and social policy - including the OECD and various bodies of the EU - also emphasize the importance of high level employment rates. The regional policy of the EU,which is targeting balanced territorial development, considers the improvement of the competitiveness of its regions as the most effective tool achieving cohesion. The study contains an analysis of the GDP of the 12 member states that joined the Union in 2004 (Cyprus, Czech Republic, Estonia, Hungary, Latvia, Lithuania, Malta, Poland, Slovak Republic, Slovenia) and those in 2007 (Romania and Bulgaria) in relation with the employment rate, corporate tax, personal income tax values, imports and exports value.